Media Penelitian Psikologi Berbasis Sistem Informasi: menelisik.id (Jurnal Ilmiah Psikologi MIND SET, 2023)
So far there is no research media available, especially in the field of psychology based on information systems that can provide direct rewards to participants in the form of participant self-report results in a study. The research media that currently exist only take participant data and cannot provide rewards directly. Rewards are usually in the form of phone credits which are given randomly to participant representatives who are selected by drawing lots. This is not in accordance with research ethics. Therefore, an information system-based psychological research media is needed that can be used by many psychology researchers, such as lecturers and students, so this research is important to do. This research is divided into two stages, namely the validity and reliability testing stage of the measuring instrument which is a pioneer in this information system and the design and application stage of the information system. The measuring tool that became a pioneer to be applied to menelisik.id is the Big Five Inventory Extra Short Forms 2 (BFI-2-XS) from Soto and John (2017). The website search.id was successfully designed and applied, in accordance with the research objectives. There were 241 respondents who used the BFI-2-XS measuring tool on menelisik.id, with most being in the high category for the agreeableness dimension. In addition, respondents were also asked to fill out a user satisfaction survey for searching.id, where the result was that 51.9% of respondents were satisfied. Henceforth, researching.id will be processed by Intellectual Property Rights and made to be more user friendly for researchers, both lecturers and students of the Faculty of Psychology, University of Pancasila.